RISK AVERSION AND OVERCONFIDENCE IN GENDER PERSPECTIVE - Clara Bella Jessica Arijaya; Sautma Ronni Basana (International Journal of Financial and Investment Studies (IJFIS), 2021)
This study analyzes the relationship between gender and risk aversion and overconfidence in making financial asset investment decisions for investors in Surabaya. The sample in this study amounted to 179 investors. Data were collected using a questionnaire. Methods of data analysis were performed using cross-tabulations and chi-square. This analysis shows that gender has a significant relationship with risk aversion and overconfidence in making financial asset investment decisions.